2017
DOI: 10.1103/physrevb.95.060407
|View full text |Cite
|
Sign up to set email alerts
|

Charge partitioning and anomalous hole doping in Rh-doped Sr2IrO4

Abstract: The simultaneous presence of sizable spin-orbit interactions and electron correlations in iridium oxides has led to predictions of novel ground states including Dirac semimetals, Kitaev spin liquids, and superconductivity. Electron and hole doping studies of spin-orbit assisted Mott insulator Sr2IrO4 are being intensively pursued due to extensive parallels with the La2CuO4 parent compound of cuprate superconductors. In particular, the mechanism of charge doping associated with replacement of Ir with Rh ions re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…This means more possibilities for emergent electronic phases [23]. Known methods for hole doping of Sr 2 IrO 4 include K doping [117] (not to be confused with K deposition discussed above) and Rh substitution in place of Ir [106,107,110,118,126,127]. Although Rh and Ir are in the same column of the periodic [129], and localization of carriers at low temperatures [106].…”
Section: Hole Dopingmentioning
confidence: 99%
“…This means more possibilities for emergent electronic phases [23]. Known methods for hole doping of Sr 2 IrO 4 include K doping [117] (not to be confused with K deposition discussed above) and Rh substitution in place of Ir [106,107,110,118,126,127]. Although Rh and Ir are in the same column of the periodic [129], and localization of carriers at low temperatures [106].…”
Section: Hole Dopingmentioning
confidence: 99%
“…Recent ARPES measurements [18] suggest that hybridization with Rh dopants dilutes the SOC present in the system, driving the system into a metallic state. On the other side, Ir and Rh L 2,3edge x-ray absorption indicates that Rh impurities assume a 3+ valence [19,20], suggesting that holes are introduced in a charge compensation process. In this picture, only a relatively small fraction of Ir ions ever assumes a 5+ oxidation state, potentially as a result of disorder on the Ir site [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the spin-orbital entanglement induced by the strong SOC in these structures could make these materials hosts for several unconventional features such as the Kitaev model [2,3], quantum spin Hall effect at room temperature [4], or unconventional superconductivity [5,6]. In addition, doped carriers in the spin-orbital entangled Mott insulating state in the iridates are expected to show many novel features and are also the subject of several recent studies [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%